Desain Media Pembelajaran Pendidikan Agama Islam pada Masa Pandemi Covid 19 di SDS Kreatif Rusyda Medan - Muhlis, Muhammad (Prodi PIAUD STAI Sumatera Medan, 2021)
This study aims to analyze the design of Islamic religious education learning media during the Covid 19 pandemic at Rusyda Creative SDS. This study uses a qualitative research method with a case study approach. Data collection techniques used observation, interviews and documentation studies, while the research informants were teachers of Islamic religious education. The results of the study showed that during the covid-19 pandemic Rusyda Creative SDS used IT-based Islamic religious education learning media designs. Because during the pandemic, teachers and students could not meet face to face. The solution offered to teachers is to design learning using IT, before that teachers are trained in advance on how to design IT-based learning media. The types of learning media are visual and audio based, and visual audio. Evaluation activities on Islamic religious education learning media during the covid 19 pandemic at Rusyda Creative SDS, using authentic assessments, which were carried out in three assessments. First attitude. The second is knowledge and the third is skills.